TAFSIR MAQASIDI TENTANG BATAS USIA PERKAWINAN - Mursyid, Ali; Hasanah, Ulfiah (Asosiasi Dosen PTKIS Indonesia, 2024)
Child marriage is a crucial problem in Indonesia. This is motivated by economic, social, cultural, and traditional factors of the community. Victims of child marriage have the potential to be trapped in a cycle of poverty because it has an impact on education and the welfare of human life. In addition, often the tradition and culture of child marriage are born from people's assumptions about religious texts both the Qur'an, hadith, and jurisprudence that are misunderstood. Meanwhile, Islam does not provide a clear age limit for marriage, thus causing differences of opinion among scholars, both tafsir scholars and jurisprudence scholars. Therefore, the author is interested in studying the ideal minimum age of marriageand maslahat in the Qur'an. This research is qualitative research based on library research. The primary sources in this study are verses of the Qur'an, books of tafsir, and the book of Naḥwa al-Tafsir al-Maqasidi li Al-Qur'an Al-Karim Ru'yah Ta'sisiyyah li Manhaj Jadid fi Tafsir Al-Qur'an by Wasfi 'Assyria Abu Zayd. While the secondary sources, are references in the form of books, journal literature, supporting articles in this study. While the approach used is a tafsir approach and to analyze the data used the theory of maqasidi tafsir designed by Waṣfi 'Assyria Abu Zayd. The results of this study show that the age limit of marriage according to the Qur'an is the age at which a person is ready for marriage which is accompanied by having maturity, physical readiness, emotional stability, and reproductive maturity. This is based onthe maqasid 'âmmah of the verses of marriage and the purpose of marriage, where the general purpose of marriage in the Qur'an is to make marriage a means of obtaining peace of mind (sakînah), as an effort to maintain and preserve offspring, and as a means of realizing interdependence and affection. This is done by behaving well and working together without losing the potential of either partner. Meanwhile, the maqasid khâṣṣah of each verse related to the age limit for marriage includes: (1) QS. Al-Nisa' (4): 6, the age of marriage is marked by puberty and having maturity (rushd). The provision of the minimum age of marriage marked by puberty must be carried out ijtihad in accordance with the conditions of community reality. (2) QS. Al-Nur (24): 32, marriage advice for single people must be accompanied by preparedness. The verse is more precisely addressed to all Muslims who are ready to carry out the burdens and responsibilities of marriage. (3) QS. AlTalaq (65): 4, this verse as a postulate plays an important role in the process of protection of women and children after thefall of talaq. Then, there is a need for a review and maturation of the age of marriage in the marriage law No. 16 of 2019, namely article 7 paragraph 1 concerning the minimum age limit of marriage of 19 years for men and women.